Determinants of Impulsive Buying in the Beauty Industry Among Young Indonesian Consumers: Examining the Moderating Effect of Fomo - Caroline Jessica Wijaya; Livia Oesef; Selica Giovani; Adilla Anggraeni (Publikasi Indonesia, 2026)
The beauty and personal care market in Indonesia has shown significant growth, driven by social media and continuous product innovation that aligns closely with consumer needs and aspirations. This study aims to analyze the determinants of impulsive buying behavior in the Indonesian beauty industry, focusing on the impact of influencer content quality and the moderating role of Fear of Missing Out (FoMO). Using the Elaboration Likelihood Model (ELM) as a theoretical framework, the study examines the influence of factors such as lifestyle-focused appearance, financial capacity, brand confidence, and impulsive buying tendencies. The analysis reveals that impulsive buying tendencies and FoMO significantly influence impulsive buying behavior. However, the findings indicate that the quality of influencer content, brand trust, and financial capacity do not significantly impact impulsive buying in the Indonesian beauty market. Overall, the study highlights the important role of emotional and psychological stimuli in unplanned purchase decision-making.